Progressivity analysis of pleomorphic adenoma toward carcinoma ex pleomorphic adenoma - Mei Syafriadi; Dina Zakiyatul Ummah; Aisyah Izzatul Muna; Maria Evata Krismawati Surya (Dental Journal (Majalah Kedokteran Gigi), 2022)
Background: Pleomorphic adenoma (PA) is a benign salivary gland tumour with high incidence and recurrence after treatment. It may recur with the same appearance or develop toward malignancy, namely as carcinoma ex pleomorphic adenoma (CXPA). Howthis tumour can transform into a CXPA remains unclear. Purpose: The aim of this study was to analyse the possibility of pathogenesis and progressivity of PA to CXPA. Methods: Twenty-four samples of PA and three control samples of CXPA were stained with haematoxylin and eosin (HE), Mallory’s trichrome, and Periodic acid–Schiff (PAS). All of the PA cases were identified through different kinds of stroma, tumour cells types, morphologic patterns, or else through atypical appearance of the PA similar to the CXPA. Results: Twenty-four samples of PA demonstrated that the most dominant stroma was myxofibrous, and the dominant tumour cell type was plasmacytoid cells with a trabecular pattern. Additionally, in the pleomorphic histological picture of adenomas we found several patterns of malignant tumour behaviour, including pseudopodia, metaplasia and hyalinisation, and cholesterol crystals that are thought to come from fat cell necrosis derived from adipose metaplasia. Conclusions: PA displays several atypical characteristics that have the potential to develop into malignancies such as CXPA, due to capsular infiltration, necrosis, hyalinization and high mitotic activity of cells, but all these atypical characteristics that we observed still cannot be clearly classified as CXPA because they require other specific examinations.